Smoking, Hemoglobin A1c and Complications in People with Type 2 Diabetes Mellitus - Saibuathong, Nampeth; Neelapaichit, Nareemarn (The Bangkok Medical Journal, 2015)
OBJECTIVES: To study the proportion of smokers in people with type 2 diabetesand to compare the glycemic control and diabetic complications of smokers, formersmokers and non-smokers. MATERIAL AND METHODS: The study was a cross-sectional descriptive study ofpatients with type 2 diabetes aged 15 years old and over who received services at theDiabetes Clinic, Outpatient Department of Internal Medicine, Ramathibodi Hospitalfrom April 2014 to January 2015. RESULTS: Of 313 participants, 2.6% of type 2 diabetes subjects were smokers, and16.3% of participants were former smokers. All smokers were males. The BMIs ofthe non-smokers and the former smokers were higher than that of the smokers (26.8,27.1 and 25.4 kg/m2, respectively). Moreover, former smokers had a higher prevalenceof being overweight (BMI > 23 kg/m2) more than the smokers and non-smokers(74.5%, 62.5% and 57.1%, respectively). The average levels of triglycerides andcholesterol in the smokers (mean was 177.0 and 192.3 mg/dL, respectively) were higherthan those of non-smokers (mean was 147.3 and 181.0, respectively) and formersmokers (mean was 142.6 and 165.1, respectively). Moreover, it was shown that theaverage of HbA1c in all groups were not different. However, the smokers were morelikely to have uncontrolled diabetes (HbA1c ≥ 7%) more than the non-smokers andthe former smokers (75.0% of the smokers, 55.9% of the non-smokers and 51.0% theformer smokers). Regarding diabetes complications, including retinopathy neuropathyand nephropathy, it was found that the smokers and the former smokers had a higherpercentage of complications than the nonsmokers. CONCLUSION: People with diabetes who smoked were more likely to have poorglycemic control and tended to have more complications than non-smokers. Therefore,in diabetic care, smoking cessation is important for glycemic control and limiting thedevelopment of diabetic complications. It is suggested that integrated care for thepatients with diabetes should be supported. That is, clear guidelines regarding the dietcontrol